The Role of Religious Argumentation in Shaping Pro-ecological Attitudes of Christians in Poland - Ryszard F. Sadowski (Studia Ecologiae et Bioethicae)
Religious arguments are an important factor influencing people’s daily choices. These choices result in, among others, relation to the natural environment and further contribute to improving or deteriorating its condition. This article is aimed at highlighting the ecological potential of Poles’ religious argumentation by presenting common arguments based on their professed faith. In addition, this study presents religious arguments used in the statements made by official representatives of the Catholic Church in Poland on environmental issues and provides examples of religiously inspired initiatives for the environment undertaken by lay Christians.